Laparoscopic Ventral Rectopexy for Obstructed Defecation: Functional Results and Quality of Life. Issue 1 (February 2021) - Degasperi, Silvia; Scarpa, Marco; Zini, Oscar; Ruffolo, Cesare; Gruppo, Mario; Bardini, Romeo; Angriman, Imerio
Abstract : Background: Laparoscopic ventral mesh rectopexy (LVR) is gaining wider acceptance as the preferred procedure to correct internal and external rectal prolapse with obstructed defecation syndrome (ODS) and/or fecal incontinence. The aim of our study was to analyze functional outcome and quality of life (Health-Related Quality of Life) after LVR for symptomatic internal prolapse and/or rectocele with ODS. Methods: Prospectively collected data on LVR for internal rectal prolapse were analyzed in 50 consecutive female patients operated between January 2011 and December 2018. In all cases, we performed a LVR according to the D'Hoore technique. Patients had ODS and internal rectal prolapse (grade 3 or 4) confirmed at the defecogram study. We registered only 1 major complication that required surgical treatment (Clavien-Dindo IIIb). The median hospital stay was 4 days [interquartile range (IQR): 2 to 5 d]. Functional results were measured with the Wexner Constipation Score and the 36-Item Short-Form Health Survey, and were analyzed before surgery and after 3, 6, or 12 months. Results: After a median follow-up of 16.5 months (IQR: 10 to 44.25 mo), the Wexner Total Score was significantly improved in almost all items passing from 14 (IQR: 11 to 18) to 11 (IQR: 6.25 to 14.75) after surgery ( P <0.0001). Incontinence was cured in 8 of 11 patients ( P =0.036). Compared with the preoperative score, the 36-Item Short-Form Health Survey score improved, especially for physical activity, varying from 75 to 87.5 ( P =0.0156). No worsening of continence status, constipation, or sexual function was observed. Conclusion: LVR appears to provide a sustained improvement in Health-Related Quality of Life, constipation, and incontinence in patients with ODS without worsening constipation with low morbidity and recurrence. Abstract : Supplemental Digital Content is available in the text.